Discurso publicitário: ação, paixão e cognição - Vasconcelos, Marilda Franco de Moura (2007)
The present study is developed in the field of discourse analysis of advertising and, since it has as theoretical referencIal the semiotics of A.J. Greimas and his disciples, focuses on the studies and semiolinguistic structures of syncretic texts of advertising whose codes are examined without their pre-existing meaning, but in the construction process of a semantic unit, in which the meaning of a language homologates that of another. The hypothesis stems from the multiculturalism that, promoting the homogenization of socio-cultural values, implies variety of products and above all, renewal of brand discourse. Corpus is constituted by advertisements of multinational companies in magazines for public with specific interests and its study aims at examining verbal-visual procedures that manifest brand interaction with such interests, according to three dimensions: pragmatic, passionate and cognitive. The analysis demonstrated that the hypotheses was confirmed, once the company diversified its products from 2003 on and above all, especially its advertising programming, creating specific texts for each target audience. However, its discourse privileged and identities pertaining to global culture, not local, since it explores the passions of man in general and examines them in view of the logic of transformations, tensions and knowledge, logic which punctuates the activities pertinent to the interests of readers of each magazine. The study evidenced few changes in linguistic structures focused on information nearly always objective and concise, but plenty of variety, originality and subtlety in the choice and combination of vision whose various resources, especially chromatic and topologic, (re)construct the verbal to reveal passions, (re)signify actions and euphemize desires